Analisis Kesenjangan Gender dalam Bidang Pekerjaan pada Era Kontemporer - Lutfiana Nisarohmah; Dadang Darmawan (UIN Sunan Gunung Djati Bandung, 2022)
The aim of this study is to discuss gender gap in the field of work. This research uses qualitative methods through library studies by applying content analysis and a psychological approach to religion. This results research and discussions include definitions of gender, gender in Islam, and gender equality in field of work. This study concluded that good religious understanding would lead to action and consistent work that is permissible in one’s religion.